Mineralogy and geochemical signatures for provenance and palaeoweathering conditions of the upper Albian Abakaliki Shale in south-eastern Nigeria - Afolabi, Olukayode Adegoke; Ogungbesan, Gbenga Olakunle; Ajibade, Olumuyiwa Michael (Geologos, 2024)
Mineralogical and geochemical studies of the Abakaliki Shale have been undertaken in order to constrain source rock composition and palaeoweathering conditions, as well as to deduce the provenance terrane types. The mineralogical analysis using X-ray diffraction has revealed an abundance of quartz and clay minerals (illite, chlorite and illite/smectite mixed layer) with a minor content of albite and gypsum. Geochemical data have demonstrated a depletion in SiO2, MnO, Y, Zr, Hf, U, Y, Cu, Ni, V, Ba and Cr and an enrichment in Rb, Sr, Th, Sc, Co, Zn and Pb in the Abakaliki Shale in comparison to the Post-Archean Australian Shale (PAAS; a proxy for the upper continental crust). Rare earth element contents generally show LREE fractionation and enrichment (LaN/YbN = 16.08–35.75 and LaN/SmN = 3.61–6.16, respectively) with a strong negative Europium anomaly (Eu/Eu* = 0.56–0.73). These geochemical characteristics suggest that the provenance of the Albian Abakaliki Shale lay in ancient upper continental crust composed mainly of felsic basement rocks with a minor contribution from mafic rocks. This is in contrast to earlier studies which suggested possible contribution of mafic components from Jurassic volcanigenic terrane as source rocks of the Albian shale in the southern Benue Trough. Moderate chemical weathering of the source rocks with mixed granite-granodiorite compositions is indicated by the value of the chemical index of alteration (average CIA 76.60); the plagioclase index of alteration (average PIA 85.20) and the index of compositional variability (average ICV 0.88), as well as by the Rb/Sr (0.32–0.92), K/Rb (125.36–193.55) and K/Na (1.13–2.70) ratios.